Plasma Sfrp5 levels correlate with determinants of the metabolic syndrome in Chinese adults. Issue 6 (18th April 2017) - Xu, Qiuyan; Wang, Hongyan; Li, Yang; Wang, Jinzhi; Lai, Yerui; Gao, Lin; Lei, Lu; Yang, Gangyi; Liao, Xin; Fang, Xia; Liu, Hua; Li, Ling
Abstract: Background: Secreted frizzled‐related protein‐5 (Sfrp5) is a novel adipokine, and it has been found to link insulin resistance with diabetes. Animal studies have revealed the role of Sfrp5 in regulating lipid and glucose metabolism. The objective of this study was to investigate the relationship between Sfrp5 and the metabolic syndrome (MetS) in a cross‐sectional study. Methods: We conducted a series of cross‐sectional studies of Chinese population including 194 control participants and 90 MetS patients. Circulating Sfrp5 concentrations were determined by ELISA. The relationships between circulating Sfrp5 levels and MetS components were assessed. Results: Circulating Sfrp5 was significantly lower in newly examined MetS patients than in control participants (49.1 ± 17.2 vs 61.6 ± 23.2 μg/L, P  < .01). Circulating Sfrp5 correlated negatively with markers of adiposity (waist‐to‐hip ratio, body mass index, and free fatty acids, P  < .001 or P  < .05). Furthermore, Sfrp5 levels correlated with fasting insulin, 2 h‐ins, fasting blood glucose, 2 h post‐glucose load blood glucose, HbA1c, and homeostasis model assessment of insulin resistance. In addition, circulating Sfrp5 levels were closely associated with blood pressure, high‐density lipoprotein cholesterol, triglycerides, and atherosclerotic index. Circulating concentrations of Sfrp5 decreased progressively with continued increases in the numbers of MetS components. The analysis of receiver operating characteristic curves revealed that the best cutoff value for circulating Sfrp5 to predict MetS was 46.8 μg/L (sensitivity 70.1 %, specificity 47.8 %, and AUC 0.66). Conclusions: We conclude that Sfrp5 may be an adipokine that is associated with the pathogenesis of MetS in humans.